Attention to Diversity in Compulsory Secondary Education - Elia Vázquez Varela; Iago Portela Pino; Víctor Domínguez Rodríguez (MDPI AG, 2020)
The attention to pupil diversity is still considered one of the main issues to solve in the current educational system. The objective of the study was to establish and analyze the differences between the knowledge and the use of ordinary and extraordinary measures in the attention to diversity from the point of view of compulsory secondary education teachers. A descriptive study was performed with a quantitative methodology, making use of a 452-teacher sample (Mean: 47, Standard Deviation: 8.42) using a survey. The results show a better understanding and frequency of use of the ordinary measures compared to the extraordinary ones. Results also maintain that among the most used we found the adequacy of the didactic planning as well as the support of the therapeutic pedagogy and language and auditory specialist. Moreover, the analysis reveals that the CMOEAD (ordinary and extraordinary measures for the attention to diversity) survey possesses psychometric properties which support its use in further studies. In conclusion, a better knowledge and use of ordinary and extraordinary measures in attention to diversity enables a forward leap in the quality and equity for pupils.